Molecular cloning and characterization of a novel splicing variant of PIASx - ZHENG Ying; ZHOU Zuo-min; YIN Lan-lan; LI Jian-ming; SHA Jia-hao (Acta Pharmacologica Sinica, 2016)
AIM: To investigate molecular mechanism of testis development and spermatogenesis. METHODS: A human testis cDNA microarray was hybridized with probes from human adult testis, embryo testis and human sperm, and the differential expressed clones were sequenced and analyzed. Expression of PIAS-NY gene was analyzed by RT-PCR. RESULT: A new isoform of PIAS family, named PIAS-NY, was isolated from human testis cDNA library. It was strongly expressed in adult testis and weakly expressed in both embryo testis and human sperm. Analysis of the open reading frame of PIAS-NY indicated that PIAS-NY was a polypeptide of 405 amino acid residues, and the sequence from the 15th amino acid to the end of PIAS-NY protein was the same as the N-terminal amino acids of PIASx-alpha and PIASx-beta protein. PIAS-NY protein contained two conserved putative LXXLL signature motifs and a zinc binding motif. Tissue distribution analysis revealed that PIAS-NY was predominantly expressed in testis, weakly in the pancreas, and almost imperceptibly in the other organs. CONCLUSION: PIAS-NY may play important role in testis development and/or spermatogenesis.